Diplomasi Indonesia Dalam Forum Indonesia – Pacific Parliamentary Partnership (IPPP) Sebagai Upaya Mengatasi Segregasi Papua - Dharma, Dewa Putu Bhagastya; Permana, Yedi Mulya; Putri, Penny Kurnia (Lenggogeni Data Publishing, 2025)
The issue of Papuan segregation is a major problem for Indonesia. Various approaches have been taken, from military intervention to negotiations, but pro-secession movements such as the Free Papua Movement (OPM) and the United Liberation Movement for West Papua (ULMWP) still receive support from a number of countries in the Pacific region. This international support is considered a threat to the country's sovereignty, so it requires a careful diplomatic approach. One alternative is being pursued through the Indonesia-Pacific Parliamentary Partnership (IPPP) forum. This study aims to analyze how and what efforts the IPPP forum has made on the Papua issue through the conceptual framework of parliamentary diplomacy and narrative power. The method used is qualitative research with data collection from official websites, meeting reports, journal articles, and related news. The results of the study show that the IPPP's efforts to cooperate and use the forum as a tool for narrative management have succeeded in influencing the decisions of Pacific countries to reduce their support for the issue of Papuan segregation. These efforts have resulted in diplomatic engagement through cooperation within the IPPP forum and the successful exertion of influence through narrative, thereby achieving the Indonesian government's objectives. These findings indicate that parliamentary diplomacy through the IPPP has had a positive impact on efforts to address the Papua issue and has become an alternative solution. Abstrak Isu segregasi Papua menjadi permasalahan besar Indonesia. Mulai dari pendekatan militer hingga negosiasi telah dilakukan, namun gerakan pro segregasi seperti Organisasi Papua Merdeka (OPM) dan United Liberation Movement for West Papua (ULMWP) masih mendapatkan dukungan dari sejumlah negara di kawasan pasifik. Dukungan internasional ini dianggap sebagai ancaman kedaulatan negara, sehingga penanganannya membutuhkan pendekatan diplomasi yang hati – hati. Salah satu alternatif yang dijalankan melalui forum Indonesia-Pacific Parliamentary Partnership (IPPP). Penelitian ini bertujuan untuk menganalisis bagaimana dan apa saja upaya yang dilakukan forum IPPP dalam isu Papua melalui kerangka konsep diplomasi parlemen dan kekuatan naratif. Metode yang digunakan adalah metode penelitian kualitatif dengan pengumpulan data dari situs resmi, laporan pertemuan, artikel jurnal, dan berita terkait. Hasil penelitian menunjukkan upaya IPPP yang melaksanakan kerja sama dan penggunaan wadah forum tersebut sebagai alat manajemen narasi yang dikeluarkan berhasil memberikan pengaruh dalam keputusan negara – negara kawasan Pasifik dalam meredam dukungannya terhadap isu segregasi Papua. Upaya ini memberikan keterlibatan diplomatik melalui kerja sama dalam forum IPPP dan keberhasilan pemberian pengaruh melalui narasi sehingga tujuan pemerintahan Indonesia berhasil dicapai. Temuan ini mengindikasikan bahwa diplomasi parlemen melalui IPPP berdampak baik kepada upaya penanganan isu Papua dan menjadi alternatif penyelesaian. Kata Kunci: Diplomasi Parlemen, IPPP, Kekuatan Naratif, Segregasi